1993
DOI: 10.1139/z93-245
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal activity in the blind mole rat (Spalax ehrenbergi)

Abstract: The locomotor activity pattern of the blind mole rat Spalax ehrenbergi was determined in its natural habitat by means of a radiotelemetric device. Twelve adult mole rats were fitted with radiotelemetric transmitters (9 during winter and 3 during summer) and tracked for 5 noncontinuous days during which air and soil temperatures were measured. Mole rats were found to have a diurnal monophasic locomotor activity pattern with activity peaks from 08:00 to 13:00 and from 11:00 to 19:00 during summer and winter, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 26 publications
1
42
0
3
Order By: Relevance
“…The absence of light underground suggests that subterranean mammals are normally deprived of the most ubiquitous zeitgeber to time life-history events, namely photoperiod. However, it has been suggested that brief exposure to light can entrain melatonin secretion in subterranean rodents (Rado et al, 1993;Reiter, Reiter et al, 1994), as it does in some other species (Reiter, 1993;Shanahan et al, 1997). In this study, melatonin secretion in a strictly subterranean rodent C. damarensis was found to be both diurnal and circadian, but relatively insensitive to acute exposure to light and dark.…”
Section: Discussionmentioning
confidence: 49%
“…The absence of light underground suggests that subterranean mammals are normally deprived of the most ubiquitous zeitgeber to time life-history events, namely photoperiod. However, it has been suggested that brief exposure to light can entrain melatonin secretion in subterranean rodents (Rado et al, 1993;Reiter, Reiter et al, 1994), as it does in some other species (Reiter, 1993;Shanahan et al, 1997). In this study, melatonin secretion in a strictly subterranean rodent C. damarensis was found to be both diurnal and circadian, but relatively insensitive to acute exposure to light and dark.…”
Section: Discussionmentioning
confidence: 49%
“…Both solitary and social mole rats typically show clear circadian rhythms and entrainment when monitored individually in the laboratory, indicating that they have a functional circadian clock [37][38][39]. Telemetry studies suggest that solitary mole-rats also show circadian rhythms under natural field conditions [39,40]. By contrast, eusocial naked mole-rats Heterocephalus gIaber and Damaraland mole-rats (Fukomys damarensis) show attenuated or no circadian rhythms, and are active around the clock when monitored in the social context of the colony [37,41,42].…”
Section: (C) Eusocial Animalsmentioning
confidence: 99%
“…Zoologists have studied mole-rat behavior extensively, and several of these studies are of particular interest to geoarchaeologists (e.g., Nevo, 1961;Bruder, 1982;Heth, 1989;Rado et al, 1993;Zuri and Terkel, 1996). Heth (1989) excavated 19 mole-rat tunnels in the Mount Carmel region of Israel and plotted their size, direction, and depth to determine if activities differed by soil type.…”
Section: Introductionmentioning
confidence: 99%